2015
DOI: 10.3892/mmr.2015.4455
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA-519 enhances HL60 human acute myeloid leukemia cell line proliferation by reducing the expression level of RNA-binding protein human antigen R

Abstract: Previous studies have demonstrated that microRNAs (miRs) are involved in cell apoptosis. However, the role of miR-519 in acute myeloid leukemia (AML) has yet to be elucidated. The present study identified the effects of miR-519 on HL60 human acute myeloid leukemia cell growth and apoptosis. The expression levels of miR-519 were examined in AML cells, as well as AML tissue samples. Furthermore, cell viability and apoptosis were examined in HL60 cells transfected with miR-519 mimics, miR-519 inhibitors or a nega… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 29 publications
1
9
0
Order By: Relevance
“…In this light, it is not surprising that HuR silencing reduced cell growth parameters in both cell lines. These results are coherent with available data on other cellular models; in fact, HuR silencing reduces cell growth of a wide range of cultured cells [ 25 28 ].…”
Section: Discussionsupporting
confidence: 90%
“…In this light, it is not surprising that HuR silencing reduced cell growth parameters in both cell lines. These results are coherent with available data on other cellular models; in fact, HuR silencing reduces cell growth of a wide range of cultured cells [ 25 28 ].…”
Section: Discussionsupporting
confidence: 90%
“…Huang et al . showed that miR-519 enhanced cell proliferation and induced cell apoptosis in AML HL-60 cell line by decreasing the level of RNA-binding protein human antigen R [14]. MiR-34a is the first identified tumor suppressor gene that is lower expressed in many forms of tumors, including breast cancer, lung cancer and AML [15-17].…”
Section: Introductionmentioning
confidence: 99%
“…To date, numerous studies have reported that abnormal expressions of miRNAs are involved in the pathogenesis and development of AL. For example, Huang, et al8 have reported that miR-519 promotes AML HL-60 cell proliferation via downregulating the expression of RNA-binding protein human antigen R. miR-34a could enhance cell apoptosis and suppress autophagy by targeting HMGB1 in AML cells 7. miR-146a has been identified to play a dual oncogenic and anticancer role in leukemia,9 because it is overexpressed in childhood ALL and AML,10 but downregulated in adult AML,11 However, the precise roles of miR-146a in AL and its potential molecular mechanism remain to be further investigated.…”
Section: Introductionmentioning
confidence: 99%